Evaluation of a Portable Wavefront Aberrometer for Community Screening Refraction in the Elderly. Issue 3 (March 2021) - Plum, William; Varadaraj, Varshini; Dosto, Niccolo; Thompson, Sean L.; Gajwani, Prateek; Friedman, David S.
ABSTRACT: SIGNIFICANCE: The SVOne may prove useful to quickly and easily assess refractive correction needs in community screenings and low-resource settings, but not all subjects were testable with the device PURPOSE: This study aimed to compare the SVOne handheld, smartphone-based wavefront aberrometer with a tabletop autorefractor in identifying refractive errors in elderly subjects. METHODS: Participants 50 years or older at community eye screenings with visual acuity worse than 20/40 in either eye underwent autorefraction followed by two SVOne trials. Power vectors of right eye data were analyzed. RESULTS: Of 84 subjects who underwent autorefraction, 67 (79.8%) were successfully autorefracted with the SVOne, of whom 82.1% (55/67) had a successful repeat reading. Mean M (spherical equivalent) values from tabletop and handheld autorefraction were −0.21 D (95% confidence interval [CI], −0.71 to +0.29 D) and −0.29 D (95% CI, −0.79 to +0.21 D), respectively ( P > .05). Mean astigmatism values from tabletop and handheld devices were +1.06 D (95% CI, 0.87 to 1.26 D) and +1.21 D (95% CI, 0.99 to 1.43 D), respectively ( P > .05). Intraclass correlation coefficients between devices were 0.95 (95% CI, 0.93 to 0.97) for M, 0.78 (95% CI, 0.66 to 0.86) for J 0, and 0.45 (95% CI, 0.24 to 0.63) for J 45 ( P < .05 for all). Excellent test-retest correlation between SVOne measurements was noted for M (Pearson correlation [ r ] = 0.96; P < .05), but a weaker correlation was noted for J 0 and J 45 ( r = 0.67 and r = 0.63 [ P < .05 for both], respectively). CONCLUSIONS: The SVOne provided strong agreement for M, with the majority of readings within ±1.00 D of each other, when compared with the tabletop autorefractor. A weaker but still good correlation was noted for astigmatism. Similar findings were noted when assessing repeatability.